2016
DOI: 10.1088/0022-3727/49/29/295204
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the electron density in plasma induced by EUV radiation: II. Numerical studies in argon and hydrogen

Abstract: We used numerical modeling to study the evolution of EUV-induced plasmas in argon and hydrogen. The results of simulations were compared to the electron densities measured by microwave cavity resonance spectroscopy. It was found that the measured electron densities can be used to derive the integral amount of plasma in the cavity. However, in some regimes, the impact of the setup geometry, EUV spectrum, and EUV induced secondary emission should be taken into account. The influence of these parameters on the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…These efforts enabled modeling plasmas induced by irradiation with one single pulse of EUV radiation. It was found that an accurate set of differential cross-sections was needed for the description of the ignition of such an EUV-induced plasma, since the models' results were very sensitive to the energy distribution between the two electrons that were produced after ionization [21]. This conclusion correlates with the work of Mokrov and Riser [23], who found as well that differential cross-sections were crucial for an accurate description of ionization coefficients.…”
Section: Recent Numerical Work On Euv-induced Bulk Plasmassupporting
confidence: 60%
See 1 more Smart Citation
“…These efforts enabled modeling plasmas induced by irradiation with one single pulse of EUV radiation. It was found that an accurate set of differential cross-sections was needed for the description of the ignition of such an EUV-induced plasma, since the models' results were very sensitive to the energy distribution between the two electrons that were produced after ionization [21]. This conclusion correlates with the work of Mokrov and Riser [23], who found as well that differential cross-sections were crucial for an accurate description of ionization coefficients.…”
Section: Recent Numerical Work On Euv-induced Bulk Plasmassupporting
confidence: 60%
“…The next steps included the development of an EUV-induced plasma tailored two-dimensional particle-in-cell code, which several experiments validated [21,22]. These efforts enabled modeling plasmas induced by irradiation with one single pulse of EUV radiation.…”
Section: Recent Numerical Work On Euv-induced Bulk Plasmasmentioning
confidence: 99%
“…The spectrum has been published by Astakhov and Van der Horst. 21,23 98% of the radiation energy is within the 10 to 20 nm bandwidth. In the past, the transmission of multiple SPFs has been measured to ensure that the transmission is not SPF specific.…”
Section: Methodsmentioning
confidence: 99%
“…41 Numerical simulations have shown that at 5 Pa, approximately one electron impact ionization takes place for each photoionization. 23 Therefore, the contribution of dissociative electron impact ionization is roughly equal to that of double photoionization.…”
Section: B Energetic Tailmentioning
confidence: 99%
See 1 more Smart Citation